1997
DOI: 10.1023/a:1006045824191
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The cost efficacy of village level eye services needs to be evaluated and the awareness of these services increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Several studies have shown financial constraints, transport difficulties, and lack of time to be barriers to attending for surgery [7],[12]–[14]. Thirdly, in many regions many patients (often the majority) refuse the offer of surgery, even when major barriers are addressed by the provision of free surgery at community level [7],[13][15]. It is likely that in the next 5 y at least, the overwhelming majority of people with TT will not receive surgical treatment, irrespective of whether the TT is minor or major.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown financial constraints, transport difficulties, and lack of time to be barriers to attending for surgery [7],[12]–[14]. Thirdly, in many regions many patients (often the majority) refuse the offer of surgery, even when major barriers are addressed by the provision of free surgery at community level [7],[13][15]. It is likely that in the next 5 y at least, the overwhelming majority of people with TT will not receive surgical treatment, irrespective of whether the TT is minor or major.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Kongwa among non-acceptors in the mid-1990s identified barriers to uptake as transportation to surgical sites, cost of surgery, arranging for the care of family and/or farm work while the patient is indisposed, and having someone to accompany the patient to the surgery site [9, 11], responses that we found continue to be important. At that time, the only surgical services were provided by local non-governmental organizations (NGOs) in the local hospital and there were no community-based surgical camps.…”
Section: Discussionmentioning
confidence: 67%
“…Based on previous research [7, 914], we developed a questionnaire on perceived barriers to accessing health care and surgical services. The questionnaire was translated from English to Swahili and then back-translated from Swahili to English for comprehension, then pilot-tested in Kongwa in non-study villages and refined before administration in study villages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers to uptake include distance to travel to surgery, perceived cost of the operation, child care duties, and lack of awareness about the treatment [14]. In Tanzania, less than a fifth of women with trichiasis opted for surgery, even when it was offered for free [18]. …”
Section: Managing Trachoma: the Safe Strategymentioning
confidence: 99%